Addressing Delays from Warehouse to Retail Display Locations - Ismail Mohammed Said Al Ruqeishi; Dr. Naim Ayadi (IJRDO - Journal of Business Management, 2025)
Efficient logistics and supply chain management are vital to the success of retail operations, directly impacting inventory availability, customer satisfaction, and overall business performance. This study investigates the operational challenges within the delivery network, focusing on inefficiencies related to routing, scheduling, and communication. Through a mixed-methods approach, the research identifies critical bottlenecks and offers strategic solutions, including route optimization, real-time tracking systems, and enhanced inventory management practices. The findings underscore the importance of reducing delivery lead times and strengthening supply chain coordination to boost customer satisfaction and streamline operational efficiency, ultimately driving business growth.